2022
DOI: 10.1186/s12884-022-04516-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with home delivery in rural Sindh, Pakistan: results from the global network birth registry

Abstract: Background According to global estimates for 2017, nearly 295,000 maternal deaths occurred worldwide. Thus, approximately 810 women die every day due to pregnancy-related complications. This burden of maternal deaths in LMICs is primarily due to poor healthcare service utilization, as indicated by relatively low rates of institutional deliveries and skilled-birth attendance (SBA). We conducted this study with an aim to assess the factors associated with home delivery and its subsequent effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As expected, the IDD was higher among women who had inadequate ANC visits compared to those who had four and above visits in our study. A number of studies consistently reported that ANC utilisation was an important determinant of choice of place of delivery [ 12 , 14 , 20 , 38 , 39 ]. Often times, it is supposed that women at their contacts during ANC visits will obtain adequate information regarding their pregnancy status and possible complications, which they may encounter during childbirth and the possible management options available at the health facilities [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the IDD was higher among women who had inadequate ANC visits compared to those who had four and above visits in our study. A number of studies consistently reported that ANC utilisation was an important determinant of choice of place of delivery [ 12 , 14 , 20 , 38 , 39 ]. Often times, it is supposed that women at their contacts during ANC visits will obtain adequate information regarding their pregnancy status and possible complications, which they may encounter during childbirth and the possible management options available at the health facilities [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies consistently reported that ANC utilisation was an important determinant of choice of place of delivery [ 12 , 14 , 20 , 38 , 39 ]. Often times, it is supposed that women at their contacts during ANC visits will obtain adequate information regarding their pregnancy status and possible complications, which they may encounter during childbirth and the possible management options available at the health facilities [ 40 , 41 ]. Besides, women who have adequate ANC visits would have frequent contacts with the healthcare providers and they may develop trust and confidence to prefer delivery at the health facilities [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor educational status, low income, more than four children, and long waiting times showed associations with the perceived poor quality of healthcare services. Women who had given birth to two or more children were less likely to give birth in a medical facility than women who were giving birth for the first time, thus showing their dissatisfaction with the services provided [ 8 ]. The influence of education is significant, as women who have completed secondary or higher education had three times the likelihood of giving birth in a medical facility.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the onset of the pandemic, maternal and child health programs in the country faced challenges such as inadequate implementation of policies, administrative issues, human resource shortages, inconsistent supplies, and failure to provide high-quality maternal care [ 7 ]. Of expectant mothers, 50% in the rural areas of the country prefer deliveries at home by traditional birth attendants, because they believe that the quality of services offered at these public health facilities, the way they are treated by the healthcare providers, and the number and skills of staff at public facilities are not adequate [ 8 ]. This perceived poor quality results in delayed engagement or non-attendance during the antenatal period, poor birth preparedness, and complication readiness, and then leads to unwanted pregnancy outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India, the proportion of IUGR is 54%. The actual incidence of IUGR in our country remains unveiled due to a large number of home deliveries where there is no concept of weighing the baby at birth (8,9) . An early diagnosis of IUGR is essential and helpful in optimizing antenatal and perinatal feto-maternal care.…”
Section: Introductionmentioning
confidence: 99%